Pore Structure Control of Ordered Mesoporous Silica Film Using Mixed Surfactants - Ha, Tae-Jung; Im, Hyeon-Gyoon; Yoon, Seok-Jin; Jang, Ho Won; Park, Hyung-Ho (HINDAWI LTD, 2011)
Materials with nanosized and well-arranged pores have been researched actively in order to be applied to new technology fields. Especially, mesoporous material containing various pore structures is expected to have different pore structure. To form a mixed pore structure, ordered mesoporous silica films were prepared with a mixture of surfactant; Brij-76 and P-123 block copolymer. In mixed surfactant system, mixed pore structure was observed in the region of P-123/(Brij-76 + P-123) with about 50.0wt.% while a single pore structure was observed in regions which have large difference in ratio between Brij-76 and P-123 through the X-ray diffraction analysis. Regardless of surfactant ratio, porosity was retained almost the same. It is expected that ordered mesoporous silica film with mixed pore structure can be one of the new materials which has distinctive properties.
Keywords: TEMPERATURE; MCM-48; ADSORPTION; COPOLYMERS; STABILITY; TEMPLATE